Child is A Teacher: Family Experience with a Child with Autism Spectrum Disorder - Ni Wayan Yuli Anggreni Anggreni; Putu Ayu Onik Pratidina; Ni Made Ayu Yuli Pratiwi; Ni Nyoman Imas Pradnyanita Wistarini; Ayu Rahmadita Apsari (Psikostudia : Jurnal Psikologi, 2025)
Families with children diagnosed with autism spectrum disorder faced various emotional, social, and economic challenges that affected their daily lives. The process of accepting their child's condition was marked by stress, anxiety, and the need for adaptive coping strategies. This study aimed to understand family experiences in dealing with and adapting to the condition of children with autism spectrum disorder, as well as to identify the coping strategies they used to manage these challenges. This research employed a qualitative approach using phenomenological methods, involving in-depth interviews with parents of children with autism spectrum disorder. Thematic analysis was conducted to explore experiences, challenges, and coping strategies applied by families. The findings revealed that families went through various emotional stages before reaching full acceptance, with coping strategies varying from social support and religious-based approaches to problem-solving strategies. This study highlighted the importance of psychosocial support and policies that address the needs of families in supporting children with autism. The implications of this research encouraged the development of more comprehensive community-based intervention programs to improve the psychological well-being of families and the quality of life of children with autism spectrum disorder. Keluarga dengan anak yang mengalami gangguan spektrum autisme menghadapi berbagai tantangan emosional sosial dan ekonomi yang mempengaruhi dinamika kehidupan mereka. Proses penerimaan terhadap kondisi anak diwarnai oleh stres kecemasan serta kebutuhan akan strategi koping yang adaptif. Studi ini bertujuan memahami pengalaman keluarga dalam menghadapi dan beradaptasi dengan kondisi anak yang memiliki gangguan spektrum autisme serta mengidentifikasi strategi koping yang digunakan dalam mengelola tantangan tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi melibatkan wawancara mendalam kepada orang tua yang memiliki anak dengan gangguan spektrum autisme. Analisis tematik dilakukan untuk menggali pengalaman tantangan serta strategi koping yang diterapkan oleh keluarga. Hasil penelitian menunjukkan bahwa keluarga melalui berbagai tahap emosional sebelum mencapai penerimaan penuh dengan strategi koping yang bervariasi mulai dari dukungan sosial pendekatan berbasis agama hingga strategi berbasis pemecahan masalah. Studi ini menyoroti pentingnya dukungan psikososial dan kebijakan yang memperhatikan kebutuhan keluarga dalam mendampingi anak dengan autisme. Implikasi dari penelitian ini mendorong pengembangan program intervensi berbasis komunitas yang lebih komprehensif guna meningkatkan kesejahteraan psikologis keluarga serta kualitas hidup anak dengan gangguan spektrum autisme.